2018
DOI: 10.1080/1061186x.2018.1523418
|View full text |Cite
|
Sign up to set email alerts
|

Development of nanoparticulate systems with action in breast and ovarian cancer: nanotheragnostics

Abstract: The use of nanoparticulate systems with action in breast and ovarian cancer has been highlighted in recent years as an alternative to increasing the therapeutic index of conventional anticancer drugs. Thus, nanoparticles have advantageous characteristics in the treatment of cancer. Several nanocarriers of drugs and nanoparticles are described in the literature. The pharmacokinetics of the drugs can be modified by the use of nanocarriers, which in turn facilitate the specific delivery of the drug to the tumour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 107 publications
0
7
0
Order By: Relevance
“…Breast cancer and ovarian cancer are the most frequently occurred gynecological cancers globally, severely threatened the life quality of females ( de Sousa Cunha et al, 2019 ; Siegel et al, 2020 ). Breast cancer has gain great attentions caused by its constantly increasing incidence despite of the improvement in treatment ( Britt et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer and ovarian cancer are the most frequently occurred gynecological cancers globally, severely threatened the life quality of females ( de Sousa Cunha et al, 2019 ; Siegel et al, 2020 ). Breast cancer has gain great attentions caused by its constantly increasing incidence despite of the improvement in treatment ( Britt et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the growing body of scientific evidence on the use of IONPs in drug delivery systems, not all relevant drugs of medical/dental interest have been investigated, either alone or in combination with IONPs [123]. In this sense, the conception of novel IONPs-based nano systems able to carry multiple drugs simultaneously and with adequate release control on the target tissues could be beneficial in several clinical situations [123,124]. These include the prevention/control of diseases associated with multiple microorganisms (e.g., bacteria and fungi), as well as conditions that require different categories of drugs (e.g., anti-inflammatory, antibiotics, and antifungal).…”
Section: Discussionmentioning
confidence: 99%
“…The micelles were conjugated with iNGR peptide to target NRP-1 receptor in TNBC. These PTX micelles showed higher uptake in TNBC than the non-targeted micelles and Taxol ® (22). Another study on PTX bounded albumin liposome (Abraxane ® ), revealed to be an effective nano-carrier to deliver the drug in TNBC.…”
Section: Passive Targetingmentioning
confidence: 96%